Error Reduction Framework for In-Line Inspection Tools Corrosion Measurements - HAMED, YAMAN (2018)
Measurements error reduction is one of the biggest concerns in metrology. Mis-estimation caused by error in measurements can lead to misleading decisions, economic and environmental loss, or system failures